Architectural review on the contemporary mosque/ masjid architecture of Malaysia: where are we heading? - Mohd Nawawi, Norwina; Abdul Majid, Noor Hanita; Jahn Kassim, Puteri Shireen; Othman, Rosniza; Md. Sharif, Harlina (2016)
The Malay World had witness evolutionary of Mosque designs from simple domestic timber structures to palatial built form of concrete, glass, and steel influenced by times, place, patron, economic and society. Lying at the crossroad between the West and Eastern trade routes, the designs of Malaysian mosques are a reflection of its society of the time and were categorized by scholars into several variants based on its influence and context. The interpretation of Mosque architecture as Islamic architecture continues to flourish the discussion by concern academics and design by practicing architects with no end. With the objective of getting on track to the very purpose why we design and built mosques as servants of Allah, this paper review the ideas and approaches of selected contemporary examples of Malaysian mosques design built within the last ten years. Through the thoughts of the designing architects and compare them to the reflective account of the scholars and academics, a forward direction based on 'beauty in its core spirituality content', resume in captivating the various stakeholders' perception of sustainable mosque architecture in a holistic sense. Mosque is a foundation to the existence of Muslim society of the place. The dynamics of the architecture must facilitate the continual spiritual embodiment of Muslims wherever they are, in whatever form or structure time and context has to offer.